2011
DOI: 10.4103/0975-7406.80776
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial activity of methanolic leaf extract of Psidium guajava L.

Abstract: Aim:This study was designed to examine the chemical composition and in vitro antimicrobial potential of methanolic extract of Psidium guajava Linn (Myrtaceae).Materials and Methods:The inhibitory effect of methanolic extract of P. guajava was tested against three bacterial and two fungal strains by using the paper disc diffusion method.Results:The methanolic extract exhibited antibacterial activity against E. coli with minimum inhibitory concentration, 0.78 μg/ml, minimum bactericidal concentration of 50 μg/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 12 publications
(12 reference statements)
2
43
0
3
Order By: Relevance
“…It interferes with the envelope subunit gp41 form the critical 6-HB structure, thus inhibit the entry of HIV into target cells. Dhiman et al 37 found that methanolic extract of P. guajava leaf has bacteriostatic and fungistatic in action. P. guajava tea showed efficient control of epidemic and pandemic influenza viruses, including oseltamivir-resistant strains, and its broad target blockage makes it less likely to lead to the emergence of viral resistance.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…It interferes with the envelope subunit gp41 form the critical 6-HB structure, thus inhibit the entry of HIV into target cells. Dhiman et al 37 found that methanolic extract of P. guajava leaf has bacteriostatic and fungistatic in action. P. guajava tea showed efficient control of epidemic and pandemic influenza viruses, including oseltamivir-resistant strains, and its broad target blockage makes it less likely to lead to the emergence of viral resistance.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…[27,28] Plants belonging to myrtacea family (Psidium gaujava, and Eucalyptus tereticornis) were belived to Badrunnisa et al…”
Section: Resultsmentioning
confidence: 99%
“…[30,31,32] Previous report on phytochemical screening of Psidium gaujava [28] , indicate the presence of carbohydrates, flavinoids, glyceroids, steroids and tannins as the main constituents. In contrast the present study reveals the presence of tannins, steroids, flavinoids, terpenoids, cardiac glyceroids, alkaloids and reducing sugars with both ethanol and methanol extracts of Psidium gaujava.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…Fifty grams of this powder was then extracted with methanol using a soxhlet apparatus. (6) The extract was evaporated to dryness and the final yield was 14% which was stored in the refrigerator and fresh sterile solutions were prepared as and when required by dissolving it in normal saline.…”
Section: Materials and Methods:-mentioning
confidence: 99%